2009
DOI: 10.1177/003335490912400513
|View full text |Cite
|
Sign up to set email alerts
|

Excess Hispanic Fetal-Infant Mortality in a Midwestern Community

Abstract: SynopSiSobjective. We assessed excess fetal-infant mortality for Hispanic, non-Hispanic white, and non-Hispanic black populations in five contiguous counties of Missouri and Kansas.Methods. We conducted a perinatal periods of risk (PPOR) assessment of fetal-infant mortality using electronic linked birth-death record files from 2001 through 2005. We generated an internal reference group in accordance with established PPOR protocol. We used Kitagawa analysis to determine whether excess deaths were due to birthwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In the total sample, 50% of excess fetoinfant deaths were associated with the MHP category and 28% of fetoinfant deaths were associated with the IH category. While all previous studies have identified MHP as the major contributor to excess fetoinfant deaths, the second highest contributor varies between maternal care and infant health, depending on community [ 6 – 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the total sample, 50% of excess fetoinfant deaths were associated with the MHP category and 28% of fetoinfant deaths were associated with the IH category. While all previous studies have identified MHP as the major contributor to excess fetoinfant deaths, the second highest contributor varies between maternal care and infant health, depending on community [ 6 – 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%